2022
DOI: 10.1253/circrep.cr-22-0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Tolvaptan for Fluid Management After Cardiovascular Surgery

Abstract: Background: Perioperative management of body fluid levels after cardiovascular surgery with cardiopulmonary bypass is essential. Fluid management using tolvaptan with conventional diuretics is effective in maintaining urine output without worsening renal function. This study aimed to improve the in-out balance in the early perioperative phase using low-dose tolvaptan (3.75 mg/day). Methods and Results:This prospective, single-center, randomized, open-label study included 199 patients who underwent cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To the Editor: Matsuda et al demonstrated that post-surgical low-dose tolvaptan therapy did not shorten the time to achieving preoperative body weight compared with conventional diuretic therapy. 1 Optimal patient selection is key to successful tolvaptan therapy. In general, tolvaptan is indicated for patients refractory to conventional diuretics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: Matsuda et al demonstrated that post-surgical low-dose tolvaptan therapy did not shorten the time to achieving preoperative body weight compared with conventional diuretic therapy. 1 Optimal patient selection is key to successful tolvaptan therapy. In general, tolvaptan is indicated for patients refractory to conventional diuretics.…”
mentioning
confidence: 99%
“…In the study of Matsuda et al, most patients had preserved renal function and the response to loop diuretics in the control group was acceptable. 1 Patients with left ventricular ejection fraction <40% and those with a glomerular filtration ratio <30 mL/min/1.73 m 2 were excluded from the study. These patients may be rather good candidates for tolvaptan therapy.…”
mentioning
confidence: 99%
“…We selected hemodynamically stable patients who did not undergo dialysis and were at low risk for safety, such as those who had a glomerular filtration rate ≥30 mL/min/1.73 m 2 and left ventricular ejection fraction ≥40%. 5 The administration of tolvaptan was initiated on postoperative Day (POD) 2; this was because patients are hemodynamically unstable after cardiovascular surgery. However, the earlier initiation of tolvaptan may be clinically beneficial in fluid management, because the low-risk group was hemodynamically stable.…”
mentioning
confidence: 99%